Charge-Trapping Devices Using Multilayered Dielectrics for Nonvolatile Memory Applications - Wen-Chieh Shih; Chih-Hao Cheng; Joseph Ya-min Lee; Fu-Chien Chiu (Advances in Materials Science and Engineering)
Charge-trapping devices using multilayered dielectrics were studied for nonvolatile memory applications. The device structure is Al/Y2O3/Ta2O5/SiO2/Si (MYTOS). The MYTOS field effect transistors were fabricated using Ta2O5 as the charge storage layer and Y2O3 as the blocking layer. The electrical characteristics of memory window, program/erase characteristics, and data retention were examined. The memory window is about 1.6 V. Using a pulse voltage of 6 V, a threshold voltage shift of ~1 V can be achieved within 10 ns. The MYTOS transistors can retain a memory window of 0.81 V for 10 years.